FACTORS ASSOCIATED WITH ELECTRIC CIGARETTES USE IN STUDENTS AT SMAN 1 TAKENGON IN 2021 - Yana, Nada; Hasnur, Hanifah; Sepatini, Riza (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2023)
Background: Every year the percentage of teenagers who smoke increases, in 2011, 3.1% of teenagers smoked e-cigarettes and 1.7% of them were still found smoking tobacco cigarettes. In 2012, the percentage of teenagers using e-cigarettes increased quite drastically by 6.5%, with details of 4.1% using e-cigarettes and 2.6% using e-cigarettes (vapes) with tobacco cigarettes, while 2% of them used tobacco cigarettes. The research aims to determine factors that can influence the use of electronic cigarettes (vape) among students at SMAN 1 Takengon. Method: Analytical descriptive research using a cross- sectional design. The sample was taken by accidental sampling with a total of 40 male students. Data collection uses a questionnaire. Analysis uses univariate and bivariate analysis. Results: Bivariate analysis shows that there is a relationship between the affordability of e-cigarettes in accessing purchasing e-cigarettes (p= 0.004) and the use of e-cigarettes, and there is no relationship between knowledge, attitudes, perceptions, pocket money, and peers towards the use of e-cigarettes. Recommendation: It is recommended that the Central Aceh Regency Health Serviceto increase outreach and guidance activities  regarding the dangers of using e-cigarettes, the need for a firm stance from the Central Aceh Regency government in paying attention to age limits for the sale of e-cigarettes.